Perancangan UI/UX Prototype Aplikasi Dompet Digital Menggunakan Metode Design Thinking - Muhammad Fiqri Widiyantoro; Taufik Ridwan; Nono Heryana; Apriade Voutama; Siska (Unversitas Muhammadiyah Riau, 2023)
Along with the rapid development of technology in all sectors, technological developments also have an influence on the digitization of cash. The community has been facilitated by digital wallet technology. The use of digital wallets itself is increasing rapidly and many new companies are establishing businesses in this field. This is because many people think that using digital wallets is a more practical way and also to reduce the number of transmission of the COVID-19 virus from cash. The purpose of the research is to designing prototype of digital wallet that can support technological advances in Indonesia and help people to facilitate their lives by making non-cash transactions, so they don't bother to carry cash everywhere. The method used in this study is Design Thinking, where Design Thinking has 5 stages in interface design, namely empathize, define, ideate, prototype and test stages. The results of this study were obtained by evaluating the interface design that has been created with the System Usability Scale (SUS) and User Experience Questionnaire (UEQ). SUS in the study produced a value of 74, which means the prototype is acceptable and meets the criteria of user needs. Meanwhile, the UEQ obtained in this study produced average results above 0.8 which means that aspects of attractiveness, clarity, efficiency, accuracy, stimulation, and novelty managed to be at a positive evaluation level, and the benchmark results in UEQ also showed that the prototype received an Excellent score in the aspects of Attractiveness, Stimulation and Accuracy, but for aspects of Clarity, Efficiency, and Novelty gets a Good grade. From the results of benchmark measurements using the UEQ questionnaire, it can be concluded that the SiDoempet prototype has a very good benchmark level overall.